Penggunaan Mikroorganisme Dalam Pengelolaan Limbah Pertanian Untuk Meningkatkan Kesuburan Tanah - Gulo, Selvian Suriani; Gea, Rosmawati; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
Agricultural waste generated from the crop production process can be a valuable resource if managed properly. The use of microorganisms in the treatment of agricultural waste has proven effective in improving soil fertility. Bacteria, fungi, and actinomycetes are examples of microorganisms that can make organic matter more easily digested by humans. The objective of this study was to analyze the role of microorganisms in agricultural layers and their moisture in relation to soil fertility. The findings of this study show that the use of microorganisms in agricultural composting and fermentation processes increases the amount of nutrients in the soil, improves soil structure, and increases its microbiological activity. This approach not only increases productivity but also reduces environmental degradation,